AL-QURAN DAN INTERPRETASI IDEOLOGIS - M. Taufiq Hidayat; Yusuf Rahman (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2022)
This paper proves that the ideological construction of an interpretation will determine the tendency of a product of interpretation and has the potential to reduce the meaning of a text and even reject other interpretations. The product of such interpretation is only more concerned with the process of elaborating verses for certain interests by designing themes and sub-themes as well as tendentious conclusions and even blaming "infidel" Muslims who are not in line, intolerant of differences of opinion, partial and fanatical which are full of radical ideologies. The findings in this article prove that the construction of Rokhmat S. Labib's interpretation is more of a process of elaborating verses for certain interests by designing themes and sub-themes with tendentious conclusions and even blaming "infidels" Muslims who are impartial, intolerant of differences, partial and fanatical. . The interpretation is often separated from the context of the verse, which causes this work to be inconsistent in taking references even though it does not ignore the historical context of the verse. This article also proves that the author's background determines ideological tendencies and interests in an interpretation